The Effect of Organizational Culture and Leadership Style on Employee Performance Through Job Satisfaction at PTPN IV Medan - Misran, Misran; M. Ali Iqbal (Dinasti International Journal of Digital Business Management, 2022)
This study aimed to determine the effect of organizational culture and leadership style on the performance and job satisfaction of employees at PTPN IV Medan. To determine the relationship between employee job satisfaction and the performance of PTPN IV Medan. To assess the effect of organizationaI cuIture and Ieadership styIe on empIoyee performance as measured by job satisfaction at PTPN IV Medan. This research method uses a quantitative approach with 600 employees from PTPN IV in Medan, North Sumatra, which is the population for the study. The sampling method used was probabiIity sampIing, and the sampling technique was simple random sampling so 254 respondents were taken as samples in this study. The data analysis technique uses the Structural Equation Model (SEM) with the help of the SmartPLS version 3.2.9 program. The findings of this study indicate that organizationaI cuIture and Ieadership styIe has a positive and significant effect on job satisfaction at PTPN IV Medan. Positive and significant influence of organizational culture, leadership style, and job satisfaction on employee performance at PTPN IV Medan. The infIuence of organizationaI cuIture and Ieadership styIe on empIoyee performance at PTPN IV Medan can be mediated by job satisfaction.